Structural characterization of the cell wall D-glucans isolated from the mycelium of Botryosphaeria rhodina MAMB-05 - Corradi da Silva, Maria de Lourdes [UNESP]; Fukuda, Eliane K.; Vasconcelos, Ana Flora D. [UNESP]; Dekker, Robert F. H.; Matias, Andreza C. [UNESP]; Monteiro, Nilson K. [UNESP]; Cardoso, Marilsa S. [UNESP]; Barbosa, Aneli M.; Silveira, Joana L. M.; Sassaki, Guilherme L.; Carbonero, Elaine R. (Elsevier B.V., 2008)
Three D-glucans were isolated from the mycelium of the fungus Botryosphaeria rhodina MAMB-05 by sequential extraction with hot-water and hot aqueous KOH (2% w/v) followed by ethanol precipitation. Following their purification by gel permeation chrornatography on Sepharose CL-4B, the structural characteristics of the D-glucans were determined by FT-IR and C-13 NMR spectroscopy and, after methylation, by GC-MS. The hot-water extract produced a fraction designated Q(1A) that was a beta-(1 -> 6)-D-glucan with the following structure:[GRAPHICS]The alkaline extract, when subjected to repeated freeze-thawing, yielded two fractions: KIP (insoluble) that comprised a beta-(1 -> 3)-D-glucan with beta-D-glucose branches at C-6 with the structure:[GRAPHICS]and K1SA (soluble) consisting of a backbone chain of alpha-(1 -> 4)-linked D-glucopyranosyl residues substituted at O-6 with alpha-D-glucopyranosyl residues:[GRAPHICS](c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Botyryosphaeria rhodina MAMB-05; fungal cell wall polysaccharideS; D-glucans